Systematic review: the etiology of esophageal squamous cell carcinoma in low-income settings. (2nd January 2019) - Chetwood, John David; Garg, Priya; Finch, Peter; Gordon, Melita
ABSTRACT: Introduction : Esophageal carcinoma causes over 380 000 deaths per year, ranking sixth worldwide in mortality amongst all malignancies. Globally, the squamous cell subtype is most common and accounts for 80% of esophageal cancers. Nonetheless, esophageal squamous cell carcinoma is much more poorly understood than esophageal adenocarcinoma, including what is driving such high prevalences, why it often presents in young patients, and shows such marked geographical delineations Areas covered : The current literature was searched for articles focusing on aetiopathogenesis of squamous cell esophageal carcinoma via a systematic review, particularly in low-resource settings. This was supplemented by papers of interest known to the authors. Expert commentary : Current putative mechanisms include polycyclic aromatic hydrocarbons, nitrosamines, acetaldehyde, cyclo-oxygenase-2 pathways, androgen and their receptor levels, as well as smoking & alcohol, micronutrient deficiencies and diet, mycotoxins, thermal damage, oral hygiene and microbiotal factors, inhaled smoke, viral infections such as HPV, and chronic irritative states. Etiology is likely multifactorial and varies geographically. Though smoking and alcohol play a predominant role in high-income settings, there is strong evidence that mycotoxins, diet and temperature effects may play an under-recognized role in low and middle-income settings.